(3bQI Yjhf GdehMOjf TQM cJGH GdJhMjOs - (3YHO GdQMef Hf GdMSf, YHO GdQMef Hf MSf Hf eMeO, J (B1285 (3g`s ((3SdjeGf Hf SMeGfs)
(3ChdgG (B:s
(3HYO GdHSedI bhdg aj cJGH GdJhMjO GdcdGe Ydi GdHSedI Hjf ePchQ aj GdTQM hGdHOGAI HgG SfI ceG aYd GdHNGQj hZjQg ef GdYdeGA GJHGYG ddSfI aj eQGSdGJ GdfHj Udi Gddg Ydjg hSde ddedhc hZjQges
(3BNQgG (B:s
(3agOi Gddg gPG GdEeGe Edi eYQaI CfhGY GdJhMjO abQQgG HCOdJgG addg GdMeO Ydi Jhajbg hgOGjJg Edi GdMb Mjf GTJOJ ZQHI GdESdGe aVd Yfg ef Vd ef Cgd GdbQi hGdCeUGQ hZjQge hHGddg GdJhajbs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3 / 304s
(3eYLe GdeDdajf (B2 / 88s
(3EjVGM Gdecfhf (B2 / 172s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds